تنمية الإبداع في مؤسسات التعليم الثانوي في ضوء التربية الإسلامية : تصور مقترح - الكناني، أحمد بن ضيف الله عنبر (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2019)
عنوان الدراسة: تنمية الإبداع في مؤسسات التعليم الثانوي في ضوء التربية الإسلامية. (تصور مقترح). بحث مكمل لنيل درجة الدكتوراه في الأصول الإسلامية للتربية. اسم الباحث: أحمد بن ضيف الله عنبر الكناني. المنهج المستخدم: المنهج الوصفي. نتائج الدراسة: 1. تطوير الأفكار، وممارستها يسهم في تنمية الإبداع. 2. تحفيز الطلاب وتشجيعهم على القيام بالأعمال الإبداعية، يشجعهم على المثابرة، ومواصلة الإبداع، ووضع آليات للاهتمام المتواصل بالمبدعين. 3. توجد معوقات شخصية وبيئية، تعيق عملية تنمية الإبداع. 4. أكثر الأساليب في تنمية الإبداع: أسلوب العصف الذهني، وأسلوب لعب الأدوار، وأسلوب التخيل. 5. ثقافة الحوار مهمة جدا لتنمية العملية الإبداعية. 6. تقوم البيئة المدرسية، والأنشطة الصفية، وغير الصفية دورا هاما في تنمية الإبداع لدى الطلاب. توصيات الدراسة: 1. على الإدارة المختصة تطوير المناهج التعليمية بما يتوافق مع العملية الإبداعية لدى الطلاب. 2. دراسة معوقات الإبداع الشخصية والبيئة للموهوبين التي تتمثل في الضغوط الدراسية وعدم تطوير المناهج المدرسية، ووجود قصور في إعداد المعلم. 3. تحفيز الطلاب، وتشجيعهم على القيام بالأعمال الإبداعية، ووضع آليات للاهتمام المتواصل بالمبدعين. 4. تدريب المعلمين على أساليب وطرق الإبداع، مثل: أسلوب العصف الذهني والقبعات، ولعب الأدوار، وكيفية استخدامها لدى الطلاب؛ لتنمية العملية الإبداعية لديهم. 5. العمل على توفير الحرية، وثقافة الحوار، وتقبل الأفكار الجديدة للطلاب؛ لتنمية العملية الإبداعية لديهم. 6. الاهتمام بالبيئة المدرسية، والأنشطة الطلابية الصفية، وغير الصفية؛ لتنمية العملية الإبداعية. 7. إدخال مقررات اختيارية حول الإبداع والتفكير الإبداعي؛ لإكساب الطلبة المهارات الإبداعية، وممارستها. 8. تشجيع وتطوير البحث الميداني في موضوع الإبداع بصفة عامة، وفي كشف عوائق الإبداع لدى الطلبة في مختلف مراحل التعليم، وخاصة التعليم الثانوي.
Study Title: Innovation Development in secondary schools institutions in the light of Islamic education. A supplementary research to obtain the PhD degree in Islamic Foundations of Education Researcher Name: Ahmed bin Daifullah Anbaar Al Kinani The used method: The descriptive approach Study Results:  Creativity is a process resulting in a new work satisfies a group of people.  Creativity development entails an idea development or a practice by the teachers.  Motivate the students and encourage them to do creative work should encourage them to persevere and continue being creative, and set up mechanisms to continuously take care of creative people.  Creativity has a personal constraints as well as inner and outer environmental constraints.  Brainstorming, hats style, role-playing and relaxations all are methods of creativity.  Freedom and the culture of dialogue are very important to develop the creativity process.  School environment, classroom and non-classroom activities play an important role in the development of creativity among students.  Educational institutions has the greatest responsibility in taking care and develop creative people. The recommendations of the study: • Work on providing the freedom and the culture of dialogue and acceptance of new ideas of the students to develop the creative process in them. • The need to motivate the students and encourage them to do creative work and put the mechanism to continuously take care of creative individuals. • Work on the study of impediments to personal and environmental innovation, which is to restrict the freedom of the creative individual, academic pressures, not developing the school curriculum and not preparing the teacher. • The concerned administration of curriculum development should make it consistent with the creative process of the students. • Train the teachers on techniques and methods of creativity, such as the style of brainstorming, hats and role-playing and how to use it on students to develop the creative process in them. • The need to pay attention to the school environment as well as classroom and non-classroom activities for students to the development of the creativity process. • Introduction of a mandatory or optional courses on creativity and creative thinking to give students creative skills and how to practice it. • Encourage and develop The Field Research on the subject of Creativity in general and to identify the barriers of creativity among students at various stages of education, especially secondary education
Keywords: التعليم الثانوي -- المؤسسات التعليمية -- التربية الإسلامية -- تنمية الإبداع -- المناهج التعليمية